Development of a success model for Water Management Information Systems - Amoako, Gordon Nana Kwesi (Department of Information Systems, 2019)
The management of water resources traverses many disciplines and involves multiple stakeholders. Water Management Information Systems (WMIS) is a combination of technological resources - software and hardware - and tools implemented to enhance the roles and functions, and the decision-making processes of water resource management. WMIS have been acknowledged to be a critical actor and part of the water resources management processes. Though the water resources management literature presents substantial evidence to back this claim, there is insufficient evidence of research in the IS literature to understand factors that affect the success of WMIS implementations. More importantly, due to the complexity of managing the resource, factors surrounding the systems and organisational context of water management institutions affect its implementations. The aim of this study is thus to develop, test and validate a model for understanding WMIS success in the water resources management context. This integrated model combines the system and organisational factors to develop the success model. The WMIS success model was conceptualized and operationalised based on the principles of water resources management, specifically the Integrated Water Resources Management (IWRM), and two IS models - HOT-Fit Framework and DeLone and McLean IS success model. The model consisted of the system and organisational factors, and a set of outcome constructs or net benefits - WMIS for Water Management Operations and WMIS for Water Management Decision-Making - that represented WMIS success. The system factors consisted of five dimensions namely; WMIS System Quality, WMIS Information Quality, Service Quality, System Use and User Satisfaction; whereas the organisation factors consisted of Leadership, Structure and Environment constructs. The model was tested and validated using cross-sectional data collected from users of WMIS from various designations of the Department of Water and Sanitation in the City of Cape Town metropolitan municipality in Cape Town, South Africa. The study recorded a 38% response rate. To analyse and validate the model, a Partial Least Squares (PLS) approach to Structural Equation Modelling (SEM) was employed. Overall, the variance explained in WMIS for Water Management Operations was 53% whiles WMIS for Water Management Decision-Making was 12%. The model fit was deemed substantial. The direct, indirect and total effects showed that, for the system factors, User Satisfaction ( =0,69) had the strongest total effect on WMIS for Water Management Operations, whereas System Use ( =0,25) had strongest total effect on WMIS for Water Management Decision-Making; in the organisation dimension, Environment ( =0,12) had the strongest total effect on WMIS for Water Management Operations, whereas Leadership ( =0,19) had the strongest total effect on WMIS for Water Management Decision-Making. User Satisfaction ( =0,69) had the strongest direct and total effect on WMIS for Water Management Operations, whereas System Use (=0,25) had the strongest direct and total effect on WMIS for Water Management Decision-Making in the human dimension. Though some of the relationships between the constructs were new to the water management context, some of the remaining relationships were consistent with finding from other systems in the IS domain. Further, the findings suggested that Service Quality, which in the contextual sense implied system and IT support staff, must be present onsite within the water management organisations to support WMIS users. Leaders in the various designations must have both and transactional and transformational characteristics. In this regard, they must ensure that they motivate users and commend them when they produce good work that affects the outcomes. Management should also ensure that they pay attention to external environmental factors like accreditation standards that affect their operations. Finally, this research has provided empirical evidence of the development of an integrated WMIS success model that is based on IS models and water resources management principles.